2017
DOI: 10.2337/db16-0987
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin 1-1 Genotype Modulates the Association of Glycemic Control With Hippocampal Volume in Elderly Individuals With Type 2 Diabetes

Abstract: Recent evidence suggests that glycemic control is associated with cognitive function in older patients with type 2 diabetes who are carriers of the haptoglobin (Hp) 1-1 genotype compared with noncarriers. We assessed whether poor glycemic control in Hp 1-1 carriers is more strongly associated with smaller hippocampal volume than in noncarriers. Hippocampal volume was generated from high-resolution structural T1 MRI obtained for 224 participants (28 Hp 1-1 carriers [12.5%] and 196 noncarriers [87.5%]) from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Our results together with those of others 8,9 with poor glycemic control in the IDCD study 26 . There is preliminary data that Hp-1 allele has poorer regeneration after endothelial injury 27,28 , suggesting a different mechanism of haptoglobin in the coronary arteries and the brain.…”
Section: Patient Characteristicssupporting
confidence: 90%
“…Our results together with those of others 8,9 with poor glycemic control in the IDCD study 26 . There is preliminary data that Hp-1 allele has poorer regeneration after endothelial injury 27,28 , suggesting a different mechanism of haptoglobin in the coronary arteries and the brain.…”
Section: Patient Characteristicssupporting
confidence: 90%
“…Series of studies have shown that Hp 1-1 genotype also confer risk of cerebrovascular disease in both type 1 [15, 48] and type 2 diabetes [49] and may be dependent on hypertension status at baseline. In our study, the prevalence of hypertension did not differ according to the Hp phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown in older persons of white race/ethnicity with type 2 diabetes that poor glycemic control was strongly associated with hippocampal volume among those with the Hp 1-1 genotype but not among other genotypes. 35 This outcome suggests that individuals with the Hp 1-1 genotype may be more vulnerable to the deleterious influences of poor glycemic control.…”
Section: Discussionmentioning
confidence: 99%